2010
DOI: 10.1016/j.jpsychores.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and coping responses within the community health care setting towards a national outbreak of an infectious disease

Abstract: These findings could potentially inform the development of practical community mental health programs for future infectious disease outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
355
2
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(395 citation statements)
references
References 40 publications
22
355
2
16
Order By: Relevance
“…Irrespective of getting exposed or being infected people can develop a fear of falling ill or dying, excessive worry/anxiety, helplessness, tendency to blame other people who are ill. The psychiatric illnesses that people develop include depression, anxiety, panic attacks, somatic symptoms, and posttraumatic stress disorder symptoms, to delirium, psychosis and even suicidality (Hall et al, 2008;Muller, 2014;Sim et al, 2010). As already pointed out, studies done in the past reported that HCW especially those working in emergency units, intensive care units, and infectious disease wards are at higher risk of developing adverse psychiatric impact (Naushad et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of getting exposed or being infected people can develop a fear of falling ill or dying, excessive worry/anxiety, helplessness, tendency to blame other people who are ill. The psychiatric illnesses that people develop include depression, anxiety, panic attacks, somatic symptoms, and posttraumatic stress disorder symptoms, to delirium, psychosis and even suicidality (Hall et al, 2008;Muller, 2014;Sim et al, 2010). As already pointed out, studies done in the past reported that HCW especially those working in emergency units, intensive care units, and infectious disease wards are at higher risk of developing adverse psychiatric impact (Naushad et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Questions 3, 5, 10, 13, 16, 17 and 21formed the depression subscale. The total depression subscale score was divided into normal (0-9), mild depression (10)(11)(12), moderate depression (13)(14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Questions 2,4,7,9,15,19, and 20 formed the anxiety subscale.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Respondents' depression, anxiety and stress levels, measured using the DASS 21-item scale, revealed a sample mean score of 20.16 (SD = 20.42). For the depression subscale, 843 (69.7%) were considered to have a normal score (score: 0-9); 167 (13.8%) were considered to suffer from mild depression (score: 10-12); 148 (12.2%) were considered to suffer from moderate depression (score: [13][14][15][16][17][18][19][20]; and 52 (4.3%) were considered to suffer from severe and extremely severe depression (score: . For the anxiety subscale, 770 (63.6%) were considered to have a normal score (score: 0-6); 91 (7.5%) were considered to suffer from mild anxiety (score: 7-9); 247 (20.4%) were considered to suffer from moderate anxiety (score: 10-14); and 102 (8.4%) were considered to suffer from severe and extremely severe anxiety (score: .…”
Section: Survey Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one, Chilcot et al [14] show that lower consequence perception predicts non-adherence with the recommendation to restrict fluid intake in patients with endstage renal disease. In the other, Sim et al [15] report the results of their investigation into the psychosocial and coping response during the 2003 severe acute respiratory syndrome (SARS) outbreak.…”
Section: Editorialmentioning
confidence: 99%